Cancer morbidity in alcohol abusers. - Tønnesen, H. (Nature Publishing Group, 1994)
Data on the association between alcohol abuse and cancer morbidity are scarce in large cohorts of non-hospitalised alcoholic men and women. Of 18,368 alcohol abusers who entered an outpatient clinic in Copenhagen during 1954-87, 18,307 were followed and their cancer incidence was compared with that of the total Danish population. On average the 15,214 men were observed for 12.9 years and the 3,093 women for 9.4 years. The overall morbidity of cancer was increased significantly. Of the men, 1,441 developed cancer [relative risk (RR) = 1.6; 95% confidence interval (CI) = 1.5-1.7], while 182 women did (RR = 1.5; 95% CI 1.3-1.8). Significantly increased incidences were found of cancer in the tongue, mouth, pharynx, oesophagus, liver, larynx, lung and pleura and secondary cancer. The women had significantly increased risk of cervical cancer (RR = 2.0; 95% CI 1.2-3.0). The men developed prostatic cancer significantly more frequently than expected (RR = 1.4; 95% CI 1.2-1.8). The risk of melanomas (RR = 0.5; 95% CI 0.2-0.8) was significantly lower than expected. The relative risks of cancer of the stomach, pancreas, kidney and endocrine system were only slightly increased. The study group did not develop more colonic (RR = 1.0; 95% CI 0.8-1.3) or rectal cancer (RR = 1.0; CI 0.7-1.3) than expected. The risk of breast cancer in women was slightly increased (RR = 1.3; 95% CI 0.9-1.7), but not statistically significant. Thus, the associations between alcohol and cancer of the upper digestive and respiratory tract and the liver are confirmed. In addition, this study indicates an increased occurrence of cancer of the prostate gland, pleura and uterine cervix in alcohol abusers.